1997
DOI: 10.1021/ja9717469
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel-Coated Glassy Nanospheres:  A Novel Method for the Synthesis of Shell Cross-Linked Knedels

Abstract: A novel method was developed to prepare shell-cross-linked knedel-like structures (SCK's), which are double-layered polymer nanospheres, in a convenient three-step procedure:  (1) polystyrene-b-poly(acrylic acid) ((DP n )PS = 130, (DP n )PAA = 120) copolymer was prepared by sequential anionic polymerization of styrene and tert-butyl acrylate, followed by hydrolysis; (2) the amphiphilic block copolymer was allowed to self-assemble into spherical multimolecular micelles in a water and THF solvent mixture; (3) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
242
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(247 citation statements)
references
References 27 publications
2
242
0
2
Order By: Relevance
“…DLS measurements (29) confirmed that the SCK/DNA aggregates formed while in solution and provided for The hydrodynamic diameter distribution of the DNA used to prepare SCK/DNA complexes was also characterized by DLS. Unlike the SCK component of the complexes, the diameter distribution of the DNA component was extremely broad.…”
Section: Resultsmentioning
confidence: 68%
“…DLS measurements (29) confirmed that the SCK/DNA aggregates formed while in solution and provided for The hydrodynamic diameter distribution of the DNA used to prepare SCK/DNA complexes was also characterized by DLS. Unlike the SCK component of the complexes, the diameter distribution of the DNA component was extremely broad.…”
Section: Resultsmentioning
confidence: 68%
“…If one block bears reactive functional groups, the morphologies of the aggregates can be fixed by chemical cross-linking. [32][33][34] In particular, shell cross-linked (SCL) micelles combine the properties of micelles, microgels, nanoparticles, and dendrimers, and various applications such as targeted drug delivery, sequestration of metabolites, and entrapment of environmental pollutants have been suggested. [35][36][37][38][39] The first example of SCL micelles was described by Wooley and co-workers, who oligomerized pendent styrene groups by using free radical polymerization chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…All the copolymers were prepared in laboratories by living polymerization, particularly, sequential anionic polymerization. [1][2][3][4][5][6][7][8][9][10] However, the preparation of such re- † To whom correspordence should be addressed. quired block copolymers is usually costly and timeconsuming.…”
mentioning
confidence: 99%
“…Recently Wooley and coworkers have reported the synthesis of shell crosslinked "knedel" (SCK) micelles. [1][2][3][4][5] SCK's belong to a new class of nanomaterials which resemble polymer micelles in their core-shell morphology as well as dendrimers and arborescent polymers in being covalently bound and stable structures. 2 Various applications in areas as diverse as solubilization, catalysis, fillers, coatings, and delivery have been proposed for these fascinating new materials.…”
mentioning
confidence: 99%